Does Tadalafil Increase The Uptake of Finasteride into Prostate Tissue? A Biochemical and Histological Evaluation in Rats - Gok, Alper; Tuygun, Can; Türkmenoglu, Tugba Taskin; Gök, Gamze; Avc?oglu, Gamze; Nural, Cemil; Kartal, Ibrahim Güven; Sagnak, Azmi Levent; Karabacak, Osman Raif; Topaloglu, Hikmet; et al. (Urology Journal, 2018)
Purpose: To histopathologically and biochemically evaluate the hypothesis that tadalafil increases the uptake of a second medication into the prostate tissue by increasing the blood supply in the prostate. Methods: Forty 12-week-old Sprague Dawley male rats were equally divided into 5 groups and were administered drugs orally as follows: Group 1 – no drugs, Group 2 – 10 days of finasteride, Group 3 – 10 days of finasteride + tadalafil, Group 4 – 30 days of finasteride, and Group 5 – 30 days of finasteride + tadalafil. At the end of 10 days of drug administration in Group1, 2, and 3, and at the end of 30 days of drug administration in Group 4 and 5, blood samples were collected from rats and analyzed for serum androgen levels. In addition, prostate tissues were removed for histological examination. Results: The mean DHT level as well as the minimum and maximum epithelial thicknesses in Group 3 were lower than those in Group 2. However, there was no statistical significant difference (P = 0.989, P = 0.176, and P = 0.070, respectively). The mean DHT level as well as the minimum and maximum epithelial thicknesses in Group 5 were lower than those in Group 4. However, there was no statistical significant difference (P = 0.984, P = 0.147, and P = 0.478, respectively). The mean minimum and maximum epithelial thicknesses in Group 3 and Group 4 were not statistically different (P = 0.488 and P = 0.996, respectively). Conclusion: The similarity of the mean minimum and maximum epithelial thickness in Group 3 and Group 4 may be indicate that the combination therapy provides an early histological effect. However, the fact that there was no statistical significant difference between Group 2 and Group 3, and between Group 4 and Group 5, in terms of the mean DHT level and minimum-maximum epithelial thicknesses suggests that longer term studies with more rats are necessary to test the validity of our hypothesis.